2012
DOI: 10.2478/s11658-011-0042-8
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of biogenic membrane flippase activity in reconstituted ER proteoliposomes in the presence of low cholesterol levels

Abstract: Abstract:Biogenic membranes or self-synthesizing membranes are the site of synthesis of new lipids such as the endoplasmic reticulum (ER) in eukaryotes. Newly synthesized phospholipids (PLs) at the cytosolic leaflet of ER need to be translocated to the lumen side for membrane biogenesis and this is facilitated by a special class of lipid translocators called biogenic membrane flippase. Even though ER is the major site of cholesterol synthesis, it contains very low amounts of cholesterol, since newly synthesize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
2
0
0
Order By: Relevance
“…The scrambling activity was lower when Chol was present in the membrane (Fig. 6, C and D), showing that the Chol ordering effect hampers the transbilayer distribution of lipids, in agreement with other studies (44)(45)(46).…”
Section: Solid-phase Binding and Mono-/bilayer Insertion Measurementssupporting
confidence: 92%
“…The scrambling activity was lower when Chol was present in the membrane (Fig. 6, C and D), showing that the Chol ordering effect hampers the transbilayer distribution of lipids, in agreement with other studies (44)(45)(46).…”
Section: Solid-phase Binding and Mono-/bilayer Insertion Measurementssupporting
confidence: 92%
“…We hypothesize that defective cholesterol removal mechanism might have led to the retention of cholesterol, which would have subsequently inhibited the flippases that modulate the sperm membranes. It has been reported that cholesterol inhibits flippase activity even at very low concentrations such as 1 mol% (Rajasekharan & Gummadi 2012). To check this effect, we reconstituted the whole cell and mitochondria with 15 mol% cholesterol and our results confirmed that the presence of cholesterol inhibited flippase activity only in whole cells and not in mitochondria, which is consistent with earlier reports that have shown that spermatozoa continuously modulate membrane cholesterol content during their transport and maturation (Cross 1998, Apel-Paz et al 2003.…”
Section: Discussionsupporting
confidence: 89%